Constraints in the Implementation of Digital Ethics in SMA Muhammadiyah 1 Surakarta - Roni Yudo Kuncoro; Triyanto Triyanto; Rini Triastuti (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
Globalization has brought changes in all aspects of life in the political, economic, social or cultural fields. The purpose of this study is to determine the obstacles in the application of digital ethics. This study used descriptive qualitative method. Data sources used were informants (Citizenship Education Teachers and students). Data collection techniques used were interviews and observation. Analysis of the data used is interactive model data analysis. The steps of the research procedure are the preparation stage, the data collection stage, the data analysis stage, and the preparation stage. The results showed that some students who at the time of their teaching and learning activities did not pay attention to the teacher, because they were playing mobile phones when teaching and learning activities applications that were opened to male students more often open games, but for female students more often open social media. The teacher also has the right policy by giving strict sanctions in the form of punishment so that students have good ethics during teaching and learning activities.